The Private Rates Of Return To Education In Pakistan - Mohammad , Farooq (2010)
The development of human capital especially through education and schooling is regarded as the main factor promoting the over all development of nations. The human factor is generally believed to be both an input in the production process as well as the beneficiary of production. It is theoretically and empirically proven that certain level of education and schooling is crucial for the development and progress of any nation or country. Therefore, this study has attempted to see the impact of various levels of education on earnings of the labor force in Pakistan using the 2004-05 survey data to reaffirm the importance of human capital theory.